Career development, digitalization and inclusive learning : empowering the workforce in technical and vocational education and training - Moreno Herrera, Lázaro [Herausgeber]; Gougoulakis, Petros [Herausgeber]; Teräs, Marianne [Herausgeber]; Kontio, Janne [Herausgeber] (Palgrave Macmillan, 2025)
"This edited book brings together novel studies that address the important role of Vocational Education and Training (VET) in empowering the workforce, with particular focus on career development, digitalization, and inclusive learning. The book has an international scope, including analysis from national VET systems in Europe, Latin America, and Asia. The book is of interest to researchers and students in the fields of technical and vocational education and training, adult education, VET teacher training, international and comparative education and career development." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: S 1 Stufen der Berufsbildung; G 1.3.3 Bildungs- & Erwerbsbiografien; L Lehren & Lernen; G 2.2.1 Technologisierung; I 2.2.1 Westeuropa; I 2.3.3 Lateinamerika; I 2.3.4 Asien; I 2.3.2 Nordamerika; 370; Berufsbildung; Berufliche Weiterbildung; Berufsverlauf; Laufbahnberatung; Lebenslanges Lernen; Digitalisierung; Lernen; Inklusion; Berufsbildungssystem; Argentinien; Bundesrepublik Deutschland; Finnland; Frankreich; Italien; Malaysia; Spanien; USA